Rift Valley fever MP-12 vaccine elicits an early protective immune response in mice. Issue 50 (28th November 2022) - Morrill, J.C.; Peters, C.J.; Bettinger, G.E.; Palermo, P.M.; Smith, D.R.; Watts, D.M.
Highlights: Development of an effective veterinary and human vaccine for RVF disease remains a high priority. RVFV MP-12 is a promising vaccine candidate for preventing RVF in humans and domestic ruminants. Adult mice vaccinated with one dose of the MP-12 vaccine was protected from lethal challenge by RVFV on days 2 through 7 post vaccination. The rapid protective immune response implied that animals could be vaccinated and protected very early during RVFV outbreaks. Overall, the findings supported the effectiveness of the MP-12 vaccine candidate for preventing RVF among humans and domestic ruminants. Abstract: Rift Valley fever virus (RVFV) is an important mosquito-borne pathogen that causes outbreaks of severe disease in people and livestock throughout Africa and the Arabian Peninsula. The development of an effective veterinary and human vaccine to protect against Rift Valley fever (RVF) disease remains a high priority. The live attenuated RVFV MP-12 is a promising vaccine candidate for the prevention of RVF in both human and domestic ruminants. The aim of this study was to determine the onset of protective immunity elicted in mice by a single dose of this vaccine. Groups of CD-1 mice were vaccinated intraperitoneally with RVFV MP-12 vaccine and challenged on days 2, 5, 6 and 7 post-vaccination (PV) with a lethal dose of virulent RVFV. The mice were observed once daily for terminal morbidity and blood samples were obtained from the retro -orbital sinus complex on days 23 and 28 PV of surviving mice to determine RVFV neutralizing antibody titers. In one test, 2 of 3 mice challenged on day 2 PV survived and all 3 mice challenged at days 5 and 7 PV also survived. A second test of 10 mice per group was performed, and half (5) of those challenged at day 2 PV survived while all (10) survived challenge at day 4 and 6 PV. All surviving animals develop antibody that ranged from 1:80 to 1:1, 280 PV. In a separate experiment, RVFV MP-12 vaccinated CD-1 mice, but not challenged developed a low viremia for the first 3 days PV and neutralzing antibody was detected on days 5 through day 28 PV. These findings demonstrated that the RVFV MP-12 vaccine elicited a rapid protective immune response in mice as early as 2 days PV, thus further supporting the effectiveness of this vaccine candidate for preventing RVF among humans and domestic ruminants.